NON-DARCY FLOW EVALUATION OF UNCONSOLIDATED POROUS MEDIA IN A CLOSED LOOP PERMEAMETER - Maciel, H. E.; Camara, L. D. T. (Revista de Engenharia Térmica, 2019)
A new closed loop permeameter was implemented in this work to study the fluid flow through two different unconsolidated porous media. An apparent permeability, similar to that proposed by Barree and Conway, was described in this work in terms of the absolute permeability combined with a new fluid property description, the inertial contribution factor that accounts for the domain of viscous and inertial forces. Such approach discriminate those properties of the rock as intrinsic permeability from those related to the fluid as the inertial contribution factor. The apparent permeability equation of Barree and Conway was applied to different intervals of the experimental data in which it was possible to obtain the Forchheimer coefficients as well as the inertial contribution factors according to each interval. Two different types of unconsolidated porous media materials were utilized in the new Closed Loop Permeameter, sand (1-2 mm) and glass spheres (3.96 mm). The equation of Barree and Conway provided a great agreement fitting the experimental data in a wide non-Darcy Reynolds number range. It was observed an increase in the Forchheimer coefficient and decrease in the apparent permeability with the flow rate increase. The results indicate a correlation between the permeability and the inertial effects in the non-Darcy turbulent regions in which the porous media materials with low permeability values are probably more subjected to flow losses due to the inertial effects.